Impact of catheter-to-vein diameter ratio on thrombosis in pediatric central venous catheterization - Kahveci, Fevzi; Çelik, Nur Ayça; Uçmak, Hacer; Gurbanov, Anar; Coşkun, Mert Kaan; Özen, Hasan; Yılmaz, Şükriye; Havan, Merve; Fitöz, Suat; Ertem, Mehmet; Kendirli, Tanıl (Frontiers in Pediatrics, 2025)
ObjectiveCatheter-related thrombosis is a common complication of central venous catheter insertion. As the use of central venous catheters increases in pediatric critical care settings, catheter-related thrombosis is becoming more common among patients who typically have multiple risk factors for thromboembolism. We aimed to investigate impact of catheter-to-vein diameter ratio on thrombosis in pediatric central venous catheterization.MethodsSingle-center, prospective study. In our study, thrombosis risk factors and patient-related factors were excluded.ResultsA total of 50 patients were included in our study. Thrombosis was observed in 34% of the patients. When comparing thrombotic and nonthrombotic patients, factors such as a low aPTT value, dialysis catheter use, certain mutations that may cause thrombosis, a high catheter-to-blood vessel diameter ratio (C/VR), and a high catheter area-to-blood vessel area ratio (C/VA) are associated with an increased risk of thrombosis. In backwards logistic regression analysis of thrombosis risk, older age, a decreased catheter area, a high C/VA ratio, and the use of dialysis catheters contributed to an increased risk of thrombosis. Patients with dialysis catheters have a 64.9 times greater risk of thrombosis than do those with central venous catheters. The C/VR, with a cut-off value of 0.197, and the C/VA, with a cut-off value of 0.088, are effective indicators in ROC analysis for thrombosis.ConclusionIn conclusion, selecting a catheter with a diameter-to-vessel diameter ratio of less than 1:5 in normovolaemic paediatric patients should be considered as a strategy to reduce the risk of catheter-related thrombosis.